A trophic cascade initiated by an invasive vertebrate alters the structure of native reptile communities. (12th March 2020) - Feit, Benjamin; Dempster, Tim; Jessop, Tim S.; Webb, Jonathan K.; Letnic, Mike
Abstract: Invasive vertebrates are frequently reported to have catastrophic effects on the populations of species which they directly impact. It follows then, that if invaders exert strong suppressive effects on some species then other species will indirectly benefit due to ecological release from interactions with directly impacted species. However, evidence that invasive vertebrates trigger such trophic cascades and alter community structure in terrestrial ecosystems remains rare. Here, we ask how the cane toad, a vertebrate invader that is toxic to many of Australia's vertebrate predators, influences lizard assemblages in a semi‐arid rangeland. In our study area, the density of cane toads is influenced by the availability of water accessible to toads. We compared an index of the abundance of sand goannas, a large predatory lizard that is susceptible to poisoning by cane toads and the abundances of four lizard families preyed upon by goannas (skinks, pygopods, agamid lizards and geckos) in areas where cane toads were common or rare. Consistent with the idea that suppression of sand goannas by cane toads initiates a trophic cascade, goanna activity was lower and small lizards were more abundant where toads were common. The hypothesis that suppression of sand goannas by cane toads triggers a trophic cascade was further supported by our findings that small terrestrial lizards that are frequently preyed upon by goannas were more affected by toad abundance than arboreal geckos, which are rarely consumed by goannas. Furthermore, the abundance of at least one genus of terrestrial skinks benefitted from allogenic ecosystem engineering by goannas where toads were rare. Overall, our study provides evidence that the invasion of ecosystems by non‐native species can have important effects on the structure and integrity of native communities extending beyond their often most obvious and frequently documented direct ecological effects. Abstract : Invasive vertebrates are frequently reported to have catastrophic effects on populations of species which they directly impact. It follows then, that if invaders exert strong suppressive effects on some species, others will be indirectly affected due to ecological release from interactions with directly impacted species. Here, we show how invasive cane toads are indirectly re‐shaping native lizard communities by reducing the activity of a large varanid lizard. Our study provides evidence that the invasion of ecosystems by non‐native species can have important effects on the structure of native communities extending beyond their often most obvious and frequently documented direct effects.